The Criticism of Utsman Najati to Modern Psychology - Muslih, Muhammad Kholid; Kholid, Husna Hisaba; Kusuma, Amir Reza; Khoerudin, Fachri (Ushuluddin, Adab, and Dakwah Faculty of State Islamic University Ponorogo, 2023)
Psychology has provided a significant effect in describing human behavior in the modern era. However, despite the extensive development of theories in modern psychology, this field of science still needs to improve in terms of terminology, epistemology, and worldview. One of the Muslim psychologists who criticized this problem was Utsman Najati. This research was library research, and the data sources consisted of primary data sources from Utsman Najati's works related to Psychology, and secondary data sources, namely in the form of books, which were relevant to this research to strengthen arguments and to complement data from research results. The data analysis technique used by the authors in this study was content analysis. The findings obtained from this paper were as follows: First, Utsman Najati revealed the disparity between the terms of psychology and research objects which were limited to behavior; Second, Utsman Najati uncovered the problem of the epistemology of psychology, which limited itself to empirical things; Third, a materialistic and atheist perspective in several schools of modern psychology contradicted the Islamic view of life.